THE EXPRESSION OF THE SYSTEMIC INFLAMMATORY RESPONSE IN PATIENTS WITH ANTERIOR ABDOMINAL WALL HERNIAS FOLLOWING THE USE OF ENDOPROSTHESES - Kuldashev G. N.; Abdurakhmanov M. M. (Modern American Journals, 2026)
In the presented study, a comprehensive analysis of the systemic inflammatory response in patients with postoperative ventral hernias is conducted, aiming to assess the bioinert properties and the impact on the cytokine profile of two different types of endoprostheses: polypropylene "Esfil" and titanium "Titan Mesh." Based on their physicochemical characteristics and interactions with biological tissues, the study extensively describes the mechanisms of implant interaction with the immune system, with a particular focus on the roles of key cytokines, including TNF-α, IL-6, IL-8, and IL-4, in the processes of healing and scar formation following surgery. The results revealed that the use of titanium Mesh is associated with reduced inflammatory activity and a lower frequency of complications compared to polypropylene prostheses, indicating its superior bioinert properties and potential to improve clinical outcomes. The importance of the micro-porous structure of titanium Mesh and its promoting effect on cell adhesion and regeneration is also discussed as a key factor in accelerating the healing processes. The study's concluding recommendations emphasize the need for further research into the influence of different endoprostheses on the inflammatory response and regenerative processes, as well as the development of new materials with optimized biocompatible characteristics to enhance the treatment of postoperative ventral hernias and improve the quality of life for patients.
Keywords: Inflammation, Ventral Hernia, Biocompatibility, Prosthetic Implants, Cytokine Profile, TNF-α, IL-6, IL-8, IL-4, Scar Formation.